Evaluasi Kualitas Manajemen Mutu pada PT Intikom Berlian Mustika dengan menggunakan ISO 9001:2015 - Vera .; Wella . (Universitas Multimedia Nusantara, 2019)
Quality Management System is crucial for companies to improve the quality of products and services produced by the companies. Therefore, companies need to gain international recognition to make the companies has a quality and good system in accordance with predetermined standards. This study uses ISO 9001:2015 as the international standard on quality management and applies in Intikom, whereas Intikom has never conducted an evaluation of the quality management system and found the employee performance is decreased recently. Due to these problems, it is necessary to evaluate and make recommendations that can be used as a guide. Evaluation of the quality management system refers to clause 4 to clause 10 of ISO 9001:2015. The used data collection technique is performing interviews to IT managers and quality management system staffs and distributing 107 questionnaires to 50 respondents for 10 divisions. The results of questionnaire were processed using the Likert scale the overall result is processed using the maturity model. The results obtained from this study of using ISO 9001: 2015 as quality standards find out that Intikom is at 4th level, which represents managed and measurable. Intikom has reached the desired target. Intikom it is ready to apply ISO 9001: 2015 and needs to improve the employee performance and products and services in order to increase to the 5th level.